2004
DOI: 10.1074/jbc.m403738200
|View full text |Cite
|
Sign up to set email alerts
|

Class II Major Histocompatibility Complex Transactivator (CIITA) Inhibits Matrix Metalloproteinase-9 Gene Expression

Abstract: Matrix metalloproteinases (MMPs) are a family of structurally related proteins with the collective capability to degrade all components of the extracellular matrix. Although MMP-mediated degradation of the extracellular matrix occurs physiologically, numerous pathological conditions exhibit increased MMP levels and excessive matrix degradation. Previous work from our laboratory has shown that interferon-␥ inhibits MMP-9 expression in a manner dependent upon STAT-1␣. Here we extend our previous observations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
(77 reference statements)
2
35
0
Order By: Relevance
“…This finding prompted us to determine whether squelching of CBP, p300, or PCAF could account for the observed inhibition of Tax-2 by CIITA. These HATs were attractive candidates in light of the fact that their squelching seems to be a common mechanism by which CIITA mediates gene suppression (69)(70)(71)(72). We found that direct sequestration of the above cofactors was not the primary mechanism by which CIITA causes suppression of Tax-2 transactivating function.…”
Section: Discussionmentioning
confidence: 74%
“…This finding prompted us to determine whether squelching of CBP, p300, or PCAF could account for the observed inhibition of Tax-2 by CIITA. These HATs were attractive candidates in light of the fact that their squelching seems to be a common mechanism by which CIITA mediates gene suppression (69)(70)(71)(72). We found that direct sequestration of the above cofactors was not the primary mechanism by which CIITA causes suppression of Tax-2 transactivating function.…”
Section: Discussionmentioning
confidence: 74%
“…Cells were grown overnight in complete medium, and then cell lysates were collected as described above. Five hundred micrograms of total protein were immunoprecipitated with 5 g of anti-p65 monoclonal antibody and analyzed by immunoblotting with anti-Flag antibody as previously described (26). Where indicated, cells were plated at 6 ϫ 10 7 cells per 15-cm plate in complete medium, in the absence or presence of Tet.…”
Section: Methodsmentioning
confidence: 99%
“…The U251-MG, U118-MG, and U87-MG glioma cell lines were obtained from ATCC and maintained as previously described (5,25,40). U251-MG cells that stably express the Tet repressor (TetR) protein and inducibly express F-ING4 or shRNA specific for p65 (sh-p65), and U118-MG cells that stably express the TetR and that inducibly express shRNA specific for ING4 (shING4) were generated as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of CBP in the presence of CIITA allowed reactivation of a Col1a1 reporter, indicating that CIITA represses the Col1a1 promoter by sequestering CBP (64). The CIITA-mediated repression of matrix metalloproteinase 9 (MMP-9) is also mediated by the sequestration of CBP by CIITA (36). Another group has shown that CIITA negatively regulates Ctse by inhibiting a related histone acetyltransferase, p300, required for CtseE promoter activity (61).…”
mentioning
confidence: 99%